A Bussiness Development of a Coffee Plantation Business Model Using the Tripple Layer Business Model Canvas - Widya Weullas; Mokh. Adib Sultan; Chairul Furqon (Jurnal Inovasi Bisnis dan Kewirausahaan, 2023)
This study aims to (1) find out the general description of the Java Frinsa Estate company, (2) formulate a strategy using SWOT analysis, and (3) make business model development proposals using the triple-layer business model canvas. This type of research is qualitative research. This study's primary data source came from observations and informants with stakeholders at Java Frinsa Estate. Secondary data was obtained from various literature and related research results. The data collection techniques used observation, interviews, and documentation carried out. The study results show that the company is in a progressive quadrant I position for business development.